Effectiveness of Sucralphate and Platelet-Rich Plasma Combinations For Vascular Endothelial Growth Factor (VEGF) Expression In Diabetic Ulcer Healing - Syaropi Simanjuntak, Victor Jeremia; Yuniati, Renni; Prajoko, Yan Wisnu; Hario Seno, Heri Nugroho; Kristina, Tri Nur (RSUP Dr. Kariadi, 2023)
Background: Diabetic ulcer is one of the most feared chronic infections due to Diabetes Mellitus because it can lead to amputation and death. Aim: To prove the effectiveness of sucralfate and platelet-rich plasma (PRP) combination for Vascular Endothelial Growth Factor (VEGF) expression in diabetic ulcer healing. Methods: This research is an experimental study of Phase I Clinical Trial with post-test only group design. There were 20 patients with diabetic ulcers divided into two groups, namely the treated group that was given sucralfate and PRP therapy and the control group was given standard therapy of normal saline drainage and gauze covered. Parameters were VEGF expression levels, wound area after being given therapy, and side effect from the treatment. Data on VEGF expression levels were obtained by means of examination with the Quantikine Human VEGF-ELISA Quantikine, R&D System, Inc, Minneapolis. The measurement of the wound area was assessed based on several criteria, namely grade 0 (no change), grade 1 (wound size reduced to less than of the previous wound), grade 2 (wound size was reduced to less than of the previous wound, but granulation was visible), and grade 3 (wound has closed completely). Result: In unpaired t-test, the mean VEGF expression was 98.18+10.96 in the treatment group and 66.69+23.79 in the control group which showed significant difference in VEGF expression levels (p = 0.003). In Mann-Whitney test, the mean wound area was 0.68+0.40 in the treatment group and 0.77+0.67 in the control group which showed that there was not any significant difference in wound area (p = 0.152). There were no side effects in both study group. Conclusions: The combination of sucralfate and PRP can increase VEGF levels significantly in diabetic ulcer patients but does not show a different effect in reducing wound area compared to standard treatment. The combination did not cause any side effects in the study subjects, as well as those using standard treatment.